Diaminobenzidine photoconversion is a suitable tool for tracking the intracellular location of fluorescently labelled nanoparticles at transmission electron microscopy - Malatesta, M.; Giagnacovo, M.; Costanzo, M.; Conti, B.; Genta, I.; Dorati, R.; Galimberti, V.; Biggiogera, M.; Zancanaro, C. (European Journal of Histochemistry, 2012)
Chitosan-based nanoparticles (NPs) deserve particular attention as suitable drug carriers in the field of pharmaceutics, since they are able to protect the encapsulated drugs and/or improve their efficacy by making them able to cross biological barriers (such as the blood-brain barrier) and reach their intracellular target sites. Understanding the intracellular location of NPs is crucial for designing drug delivery strategies. In this study, fluorescently-labelled chitosan NPs were administered in vitro to a neuronal cell line, and diaminobenzidine (DAB) photoconversion was applied to correlate fluorescence and transmission electron microscopy to precisely describe the NPs intracellular fate. This technique allowed to demonstrate that chitosan NPs easily enter neuronal cells, predominantly by endocytosis; they were found both inside membrane-bounded vesicles and free in the cytosol, and were observed to accumulate around the cell nucleus.